Droplet-engineered organoids recapitulate parental tissue transcriptome with inter-organoid homogeneity and inter-tumor cell heterogeneity - Haoran Zhao; Yifan Cheng; Jiawei Li; Jiaqi Zhou; Haowei Yang; Feng Yu; Feihong Yu; Davit Khutsishvili; Zitian Wang; Shengwei Jiang; Kaixin Tan; Yi Kuang; et al. (Fundamental Research)
Organoids are expected to function as effective human organ models for precision cancer studies and drug development. Currently, primary tissue-derived organoids, termed non-engineered organoids (NEOs), are produced by manual pipetting or liquid handling that compromises organoid-organoid homogeneity and organoid-tissue consistency. Droplet-based microfluidics enables automated organoid production with high organoid-organoid homogeneity, organoid-tissue consistency, and a significantly improved production spectrum. It takes advantage of droplet-encapsulation of defined populations of cells and droplet-rendered microstructures that guide cell self-organization. Herein, we studied the droplet-engineered organoids (DEOs), derived from mouse liver tissues and human liver tumors, by using transcriptional analysis and cellular deconvolution on bulk RNA-seq data. The characteristics of DEOs are compared with the parental liver tissues (or tumors) and NEOs. The DEOs are proven higher reproducibility and consistency with the parental tissues, have a high production spectrum and shortened modeling time, and possess inter-organoid homogeneity and inter-tumor cell heterogeneity.